Introducing a novel sham acupuncture method for double-blind trials: A validation study - Sung Min Lim; Eunji Go; Jungsup Lee; Go Eun Lee; Chihyoung Son (Complementary Therapies in Medicine)
Introduction: Various clinical studies have been conducted worldwide to evaluate the effectiveness of acupuncture; however, designing an adequate control group is challenging. Sham acupuncture tools, designed to mimic real acupuncture without skin penetration, aim to address this challenge, but their efficacy and blinding success are debated. Methods: In this study, we conducted a randomized, double-blind, parallel-group clinical trial to validate a newly developed sham acupuncture method for future double-blind trials. Sixty-six healthy participants were randomly assigned to verum or sham acupuncture groups. Verum acupuncture targeted LI4 and ST36, common acupuncture points, while sham acupuncture aimed to mimic verum without skin penetration to ensure participant blinding. Blinding (Bang’s Blinding Index), penetration, pain, and deqi sensations were evaluated using a standardized questionnaire and an 11-point Numeric Rating Scale. Results: Participant blinding was successfully maintained at ST36, whereas “more correct guesses” were observed for verum acupuncture than expected by chance for sham acupuncture at LI4. Furthermore, the practitioners randomly guessed the verum and sham acupuncture that they had administered to both points. Penetration and pain were higher in the verum group for both points, while deqi sensations had mixed responses. There were no adverse events in the verum acupuncture and sham acupuncture groups. Conclusions: The newly developed sham acupuncture demonstrated potential in blinding participants and practitioners, particularly at ST36. However, challenges were observed, especially at LI4, indicating limitations in blinding efficacy. This study underscores the importance of additional validation studies with larger sample sizes, diverse acupuncture points, and specific patient populations. Trial registration: Clinical Research Information Service of the Republic of Korea (registration number: KCT0008335, https://cris.nih.go.kr).